Berberine alleviates rotenone-induced cytotoxicity by antioxidation and activation of PI3K/Akt signaling pathway in SH-SY5Y cells. Issue 1 (8th January 2020) - Deng, Han; Jia, Yi; Pan, Dong; Ma, ZeGang
Abstract : Berberine, an isoquinoline alkaloid isolated from traditional Chinese medicine, has been widely studied for its efficacy in the treatment of neurodegenerative diseases. However, berberine-mediated neuroprotection in the pathogenesis of Parkinson's disease is still uncertain. In this study, the effects of berberine on rotenone-induced neurotoxicity in SH-SY5Y cells were investigated. The results showed that berberine treatment significantly alleviated rotenone-induced decrease in the cell viability in SH-SY5Y cells. Further studies demonstrated that berberine suppressed the production of intracellular reactive oxygen species, restored the mitochondrial transmembrane potential, increased Bcl-2/Bax ratio, and decreased caspase-3 activation that induced by rotenone. Furthermore, berberine also restored the phosphorylation of Akt, which was downregulated by rotenone in SH-SY5Y cells. These results suggest that berberine protects rotenone-treated SH-SY5Y cells by antioxidation and activation of PI3K/Akt signaling pathway. Abstract : Supplemental Digital Content is available in the text.